A partially-planarised hole-transporting quart-: P -phenylene for perovskite solar cells - Mora-Fuentes, Juan P.; Cortizo-Lacalle, Diego; Collavini, Silvia; Strutyński, Karol; Tress, Wolfgang R.; Saliba, Michael; Zakeeruddin, Shaik M.; Kosta, Ivet; Melle-Franco, Manuel; Grätzel, Michael; Delgado, Juan Luis; Mateo-Alonso, Aurelio (Journal of Materials Chemistry C, 2019)
Herein, we describe the synthesis of a hole transporting material based on a partially planarised quart-p-phenylene core incorporating tetraketal and diphenylamine substituents that show optimal energy levels and solubility for perovskite solar cell applications. The triple-cation perovskite devices incorporating such quart-p-phenylene derivatives show power-conversion efficiencies, short circuit currents, open circuit voltages, and fill factors that are comparable to those of spiro-OMeTAD.
Created from Fastlane, Scopus look-up

Circularly Polarized Luminescence in a Möbius Helicene Carbon Nanohoop** - Malinčík, Juraj; Gaikwad, Sudhakar; Mora-Fuentes, Juan P.; Boillat, Marc Aurèle; Prescimone, Alessandro; Häussinger, Daniel; Campaña, Araceli G.; Šolomek, Tomáš (Angewandte Chemie International Edition, 2022)
We present the first helicene carbon nanoohop that integrates a [6]helicene into [7]cycloparaphenylene. The [6]helicene endows the helicene carbon nanohoop with chiroptical properties and configurational stability typical for higher helicenes, while the radially conjugated seven para-phenylenes largely determine the optoelectronic properties. The structure of the helicene carbon nanoohop was unambiguously characterized by NMR, MS and X-ray analysis that revealed that it possesses a topology of a Möbius strip in the solid state and in solution. The chirality transfers from the [6]helicene to the para-phenylenes and leads to a pronounced circular dichroism and bright circularly polarized luminescence, which is affected by the structural topology of the nanohoop.
Created from Fastlane, Scopus look-up
Keywords: Chirality; Circularly Polarized Luminescence; Cycloparaphenylenes; Helicenes; Molecular Nanocarbons; Möbius Topology

Collecting up to 115% of Singlet-Fission Products by Single-Walled Carbon Nanotubes - Menon, Arjun; Papadopoulos, Ilias; Harreiß, Christina; Mora-Fuentes, Juan P.; Cortizo-Lacalle, Diego; Mateo-Alonso, Aurelio; Spiecker, Erdmann; Guldi, Dirk Michael (Acs Nano, 2020)
In this contribution, we focused on integrating a phenylene-bridged dibenzodiazahexacene dimer (o-DAD), which is singlet fission (SF) active, onto single-walled carbon nanotubes (SWCNTs) as a low-energy sink for energetically low lying excited states that stem from SF. Spectroscopic and microscopic assays assisted in documenting that SWCNT/o-DAD feature high stability in THF as a result of electronic interactions between the individual constituents. For example, statistical Raman analysis underlined n-doping of SWCNTs in the presence of o-DAD. Fluorescence spectroscopy prompted an energy transfer between the individual constituents, a conclusion that was exclusively derived from the quenching of the o-DAD-centered fluorescence. Excitation spectroscopy with a focus on the SWCNT fluorescence confirmed independently this conclusion by showing o-DAD-centered features. Our work was rounded off by time-resolved transient absorption measurements with SWCNT/o-DAD, in which evidence was gathered for the sequential o-DAD-centered SF with an efficiency of 112% followed by a unidirectional energy transfer from o-DAD to SWCNT and a rapid deactivation. The energy transfer efficiency from SF products such as (S1S0)CT and 1(T1T1) exceeded the 100% threshold with values of 115%, which is conventionally found in energy transfer scheme
Keywords: carbon nanotubes; pyrene-fused azaacenes; singlet fission; energy transfer; doping

Depositing Molecular Graphene Nanoribbons on Ag(111) by Electrospray Controlled Ion Beam Deposition: Self-Assembly and On-Surface Transformations - Ran, Wei; Walz, Andreas; Stoiber, Karolina; Knecht, Peter; Xu, Hongxiang; Papageorgiou, Anthoula C.; Huettig, Annette; Cortizo-Lacalle, Diego; Mora-Fuentes, Juan P.; Mateo-Alonso, Aurelio; Schlichting, Hartmut; Reichert, Joachim; et al. (Angewandte Chemie International Edition, 2022)
The chemical processing of low-dimensional carbon nanostructures is crucial for their integration in future devices. Here we apply a new methodology in atomically precise engineering by combining multistep solution synthesis of N-doped molecular graphene nanoribbons (GNRs) with mass-selected ultra-high vacuum electrospray controlled ion beam deposition on surfaces and real-space visualisation by scanning tunnelling microscopy. We demonstrate how this method yields solely a controllable amount of single, otherwise unsublimable, GNRs of 2.9 nm length on a planar Ag(111) surface. This methodology allows for further processing by employing on-surface synthesis protocols and exploiting the reactivity of the substrate. Following multiple chemical transformations, the GNRs provide reactive building blocks to form extended, metal–organic coordination polymers.
Created from Fastlane, Scopus look-up
Keywords: Electrospray Deposition; Graphene Nanoribbons; On-Surface Synthesis; Scanning Tunnelling Microscopy; Ultra-High Vacuum

Dibenzoanthradiquinone Building Blocks for the Synthesis of Nitrogenated Polycyclic Aromatic Hydrocarbons - Martínez, Jose I.; Mora-Fuentes, Juan P.; Carini, Marco; Saeki, Akinori; Melle-Franco, Manuel; Mateo-Alonso, Aurelio (Organic Letters, 2020)
A straightforward method for the synthesis of two dibenzo[a,h]anthracene-5,6,12,13-diquinone building blocks is reported. To showcase their usefulness, a series of dibenzo[a,h]anthracene nitrogenated derivatives have been synthesized that show different optoelectronic, redox, and charge transport properties, illustrating their potential as organic semiconductors.
Created from Fastlane, Scopus look-up

Giant Star-Shaped Nitrogen-Doped Nanographenes - Mora-Fuentes, Juan P.; Riaño, Alberto; Cortizo-Lacalle, Diego; Saeki, Akinori; Melle-Franco, Manuel; Mateo-Alonso, Aurelio (Angewandte Chemie International Edition, 2019)
Star-shaped nanographenes (SNGs) are large monodisperse polycyclic aromatic hydrocarbons that are larger than a nanometer and have shown a lot of promise in a wide range of applications including electronics, energy conversion, and sensing. Herein, we report a new family of giant star-shaped N-doped nanographenes with diameters up to 6.5 nm. Furthermore, the high solubility of this SNG family in neutral organic solvents at room temperature allowed a complete structural, optoelectronic, and electrochemical characterisation, which together with charge transport studies illustrate their n-type semiconducting character.
Created from Fastlane, Scopus look-up
Keywords: cloverphenes; nanographenes; polycyclic aromatic hydrocarbons; star-shaped nanographenes; starphenes

Helicenes. Synthesis, Properties and Applications. (Book chapter) 10. Helical Nanographenes: Synthetic and Chiroptical Achievements - Mora Fuentes, Juan Pedro; et al. (Helical Nanographenes: Synthetic and Chiroptical Achievements, 2022)
This book chapter puts helical nanographenes under the spotlight. The appealing combination of chirality and extended conjugation of these purely organic molecular designs makes them promising candidates for optoelectronic applications. Herein, the optical properties of nanographenes presenting helical motifs, both achiral/racemic and enantioenriched/enantiopure samples, have been taken into account. Besides, based on the elemental composition of their cores, examples were sorted in purely carbonated and heteroatom-doped helical nanographenes. Furthermore, a comparison at both structural and properties level was made between simple and multiple laterally-extended helicenes, paying special attention to species with non-hexagonal rings in their structures. Discussion briefly alludes to synthetic aspects, mentioning their most relevant structural features, and highlighting their chiroptical properties. These last two aspects were compiled in a table at the end of the chapter including commonly employed chirality descriptors along with structural parameters.<br

Heptagon-Containing Nanographene Embedded into [10]Cycloparaphenylene - Mora-Fuentes, Juan P.; Codesal, Marcos D.; Reale, Marco; Cruz, Carlos M.; Jiménez, Vicente G.; Sciortino, Alice; Cannas, Marco; Messina, Fabrizio; Blanco, Victor; Campaña, Araceli G. (Angewandte Chemie International Edition, 2023)
We report the synthesis and characterization of a novel type of nanohoop, consisting of a cycloparaphenylene derivative incorporating a curved heptagon-containing π-extended polycyclic aromatic hydrocarbon (PAH) unit. We demonstrate that this new macrocycle behaves as a supramolecular receptor of curved π-systems such as fullerenes C60 and C70, with remarkably large binding constants (ca. 107 M−1), as estimated by fluorescence measurements. Nanosecond and femtosecond spectroscopic analysis show that these host-guest complexes are capable of quasi-instantaneous charge separation upon photoexcitation, due to the ultrafast charge transfer from the macrocycle to the complexed fullerene. These results demonstrate saddle-shaped PAHs with dibenzocycloheptatrienone motifs as structural components for new macrocycles displaying molecular receptor abilities and versatile photochemical responses with promising electron-donor properties in host-guest complexes.
Created from Fastlane, Scopus look-up
Keywords: Cycloparaphenylenes; Host-Guest Systems; Macrocycles; Nanographenes; Transient Absorption Spectroscopy

Monodisperse N-Doped Graphene Nanoribbons Reaching 7.7 Nanometers in Length - Cortizo-Lacalle, Diego; Mora-Fuentes, Juan P.; Strutyński, Karol; Saeki, Akinori; Melle-Franco, Manuel; Mateo-Alonso, Aurelio (Angewandte Chemie International Edition, 2018)
The properties of graphene nanoribbons are highly dependent on structural variables such as width, length, edge structure, and heteroatom doping. Therefore, atomic precision over all these variables is necessary for establishing their fundamental properties and exploring their potential applications. An iterative approach is presented that assembles a small and carefully designed molecular building block into monodisperse N-doped graphene nanoribbons with different lengths. To showcase this approach, the synthesis and characterisation of a series of nanoribbons constituted of 10, 20 and 30 conjugated linearly-fused rings (2.9, 5.3, and 7.7 nm in length, respectively) is presented.
Created from Fastlane, Scopus look-up
Keywords: graphene; nanoribbons; polycyclic aromatic hydrocarbons

Singlet Fission in Pyrene-Fused Azaacene Dimers - Mora-Fuentes, Juan P.; Papadopoulos, Ilias; Thiel, Dominik; Alvarez-Boto, Roberto; Cortizo-Lacalle, Diego; Clark, Timothy; Melle-Franco, Manuel; Guldi, Dirk Michael; Mateo-Alonso, Aurelio (Angewandte Chemie International Edition, 2019)
Singlet fission has emerged as a promising strategy to avoid the loss of extra energy through thermalization in solar cells. A family of dimers consisting of nitrogen-doped pyrene-fused acenes that undergo singlet fission with triplet quantum yields as high as 125 % are presented. They provide new perspectives for nitrogenated polycyclic aromatic hydrocarbons and for the design of new materials for singlet fission.
CRIS-Team WoS Importer:2019-12-10